The Correlation Between Students’ Reading Attitude and Their Reading Comprehension - Nisak, Shabrina Ikhsanin (Journal of English Teaching, Literature, and Applied Linguistics, 2023)
The act of comprehending a text is known as reading comprehension. The aim is to fully comprehend what is being described in the text. L2 reading may be influenced by a variety of factors, one of them is reading attitude. A learner's reading attitude, which affects whether they enjoy or hate reading, may have an impact on their reading skills through how involved they are with their reading. The aim of this study is to determine whether or not reading comprehension and student attitudes are correlated. A total of 48 junior high school students in the eighth grade participated in this study. The data was collected by distributing a reading attitude questionnaire and reading comprehension TOEFL Junior Test. The result found that the students’ reading attitude was fairly good (M = 3.40) and their reading comprehension was mostly at B1 level (M = 288.35). However, the result of Pearson Correlation showed that there is a weak correlation between students’ reading attitude and their reading comprehension ( r = .279, p = 0.055). The students believe that reading can give them a positive impact, yet they do not really like the activity of reading.